Fully automated CFD simulation system research based on design scheme tree - Zijun Liu (Scientific Reports)
Abstract Compared with the remarkable achievements of computer-aided drug discovery systems for drug discovery, the role of computational fluid dynamics (CFD) in flow channel design requires further development. While CFD has undergone rapid evolution, the absence of integrated geometry and mesh processing hinders the potential development of advanced applications of this technology. To overcome this limitation, in this paper, the JIACFD toolset is presented, and a fully automated CFD simulation system is established. The simulation system is also constructed on a design scheme tree, which is more in accordance with engineering logic. The control parameter trend analysis method is introduced to select appropriate candidates from the design scheme tree. Additionally, the control parameter trend assumption, which is proven via the Spearman method, is proposed to improve the efficiency of the system. During the verification process for the study case, two independent control parameters exhibit correlating trends, and one control parameter converges when the number of meshes increases, indicating a lack of trend sensitivity. The design scheme tree and trend curve are subsequently utilized to effectively analyze the flow field characteristics of different schemes. Finally, the control parameter trend analysis method is employed to rank the design scheme tree and verify that the ranking of candidates is not dependent on the number of meshes. This paper investigates and verifies the presented system, method, and assumption and explores the possibility of an established system playing a more critical role in performance design work.